The Clinical Challenges, Trials, and Errors of Combatting Poly(ADP-Ribose) Polymerase Inhibitors Resistance. Issue 6 (November 2021) - Pham, Melissa M.; Hinchcliff, Emily; Avila, Monica; Westin, Shannon N.
Abstract: The use of poly(ADP-ribose) polymerase inhibitor (PARPi) exploits synthetic lethality in solid tumors with homologous recombination repair (HRR) defects. Significant clinical benefit has been established in breast and ovarian cancers harboring BRCA1/2 mutations, as well as tumors harboring characteristics of " BRCA ness." However, the durability of treatment responses is limited, and emerging data have demonstrated the clinical challenge of PARPi resistance. With the expanding use of PARPi, the significance of PARP therapy in patients pretreated with PARPi remains in need of significant further investigation. Molecular mechanisms contributing to this phenomenon include restoration of HRR function, replication fork stabilization, BRCA1/2 reversion mutations, and epigenetic changes. Current studies are evaluating the utility of combination therapies of PARPi with cell cycle checkpoint inhibitors, antiangiogenic agents, phosphatidylinositol 3-kinase/AKT pathway inhibitors, MEK inhibitors, and epigenetic modifiers to overcome this resistance. In this review, we address the mechanisms of PARPi resistance supported by preclinical models, examine current clinical trials applying combination therapy to overcome PARPi resistance, and discuss future directions to enhance the clinical efficacy of PARPi.